2006
DOI: 10.1167/iovs.05-0195
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Receptors in Chick Ocular Tissues: Implications for a Role of Melatonin in Ocular Growth Regulation

Abstract: Results of this study show that all three melatonin receptor subtypes are expressed in retinal and extraretinal ocular tissues of the chick eye. The finding that administration of melatonin alters the growth of several ocular tissues in both control and form-deprived eyes suggests that melatonin, acting through specific melatonin receptors in ocular tissues, plays a role in ocular growth and development. This conclusion suggests that the action of melatonin, combined with expression of melatonin receptors, is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(75 citation statements)
references
References 41 publications
4
71
0
Order By: Relevance
“…Chicken retinal Mel-1C mRNA was also found to be rhythmic in LD with high expression levels during the day but opposite phasing in DD while Mel-1B was highly variable and arrhythmic (Natesan and Cassone, 2002). A comparison of our mRNA data with melatonin receptor protein levels in the chicken retina revealed certain differences in peak expression times; while the Mel-1A receptor was found to peak at ZT12 at the transition from light to dark, Mel-1B peaked at ZT20, and Mel-1C at ZT0 in the chicken retina (Rada & Wiechmann, 2006) we found mRNA in the retina to peak at ZT18 (Mel-1A), ZT10 (Mel1B), and Mel1C mRNA to be arrhythmic. These differences could be caused by differential expression of melatonin receptors in the different layers of the retina as both studies used whole tissue samples or by species-specific differences between the role the retina plays in galliform and passeriform circadian organisation (Brandstaetter, 2002).…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…Chicken retinal Mel-1C mRNA was also found to be rhythmic in LD with high expression levels during the day but opposite phasing in DD while Mel-1B was highly variable and arrhythmic (Natesan and Cassone, 2002). A comparison of our mRNA data with melatonin receptor protein levels in the chicken retina revealed certain differences in peak expression times; while the Mel-1A receptor was found to peak at ZT12 at the transition from light to dark, Mel-1B peaked at ZT20, and Mel-1C at ZT0 in the chicken retina (Rada & Wiechmann, 2006) we found mRNA in the retina to peak at ZT18 (Mel-1A), ZT10 (Mel1B), and Mel1C mRNA to be arrhythmic. These differences could be caused by differential expression of melatonin receptors in the different layers of the retina as both studies used whole tissue samples or by species-specific differences between the role the retina plays in galliform and passeriform circadian organisation (Brandstaetter, 2002).…”
Section: Discussionmentioning
confidence: 62%
“…Studies on avian melatonin receptors mainly focused on the retina (Rada and Wiechmann, 2006), gonads (Aste et al, 2001) and song-control nuclei in the brain (Cassone et al, 2008;Whitfield-Rucker and Cassone, 1996) photoreception takes place in the retina only and there has been an evolutionary loss of two retinal cone classes (Barrett et al, 2003) and of certain opsins which are found in nonmammalian vertebrates including birds and fishes (Bellingham et al, 2003). These differences in circadian organisation are believed to be the consequence of a "nocturnal bottleneck" during early evolution of mammals (Foster et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the melatonin rhythm can be affected by many factors, light appears to have a major influence. Melanopsin, present in the ipRGCs in the retina, provides information about ambient environmental light to the SCN and hence melatonin levels appear to be influenced by retinal melanopsin signalling (Rada & Wiechmann, 2006). Melanopsin photopigment is sensitive to blue light (short wavelength) and insensitive to long wavelengths (Panda et al, 2005).…”
Section: Diurnal Ocular Variationsmentioning
confidence: 99%